Psychological Aspects of Cancer A Guide to Emotional and Psychological Consequences of Cancer, Their Causes, and Their Management - Steel, Jennifer L.; Carr, Brian I.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book addresses the unmet needs of the medical community in dealing with the psychological problems, particularly anxiety and depression, of patients diagnosed with cancer. Providing a scholarly review of the impact of cancer diagnosis on patients$1 (Bemotional and psychological status, as well as the evidence that psychological factors impact cancer occurrence and biological behavior, this book explores the therapeutic implications of such converse dynamics. Chapters review financial toxicity, eHealth, palliative care, mindfulness, sleep and cancer, social support and cancer, cultural diversity, pediatric and adolescent oncology, and geriatric oncology. While intended primarily for the professional readership of oncologists, psychologists, psychiatrists, social workers, and palliative care physicians, a final chapter also provides practical information on available resources for patients. This fully updated and expanded new edition of Psychological Aspects of Cancer: A Guide to Emotional and Psychological Consequences of Cancer, Their Causes, and Their Management provides practitioners with cutting edge knowledge as well as practical information that translates into better care for patients with cancer. .s
Inflammation, Chronic Disease, and Cancer: Is Psychological Distress the Common Thread? -- Psychological Factors and Survivorship: A Focus on Post-Treatment Cancer Survivors -- Couple Relationships and Cancer -- The Impact of Cancer and Its Therapies on Body Image and Sexuality -- Use of the Classic Hallucinogen Psilocybin for Treatment of Existential Distress Associated with Cancer -- Meaning, Spirituality, and Perceived Growth Across the Cancer Continuum: A Positive Psychology Perspective -- Stress, Coping, and Hope -- Religiousness and Spirituality in Coping with Cancer -- Psychoneuroimmunology and Cancer: Mechanisms Explaining Incidence, Progression, and Quality of Life Difficulties -- Psychosocial Interventions in Cancer -- Altruism in Relation to Live Donor Liver Transplants for Liver Cancer -- New and Emerging Challenges in Advanced Cancer Care: Opportunities for Enhancing Patient-Centered Communication -- Complementary Mind-Body Therapies in Cancer -- The Intersection between Cancer and Caregiver Survivorship -- Controversies in Psycho-Oncology -- Resources for Cancer Patients -- Adolescent and Young Adult Cancer Survivors -- Cancer Fatalism: Attitudes Toward Screening and Car -- The Intersection between Cancer and Caregiver Survivorship -- Cancer and the Aging Population -- Mindfulness Based Interventions for Patients with Cancer -- Social Genomics and Cancer: Neural Regulation of the Cancer Genome -- Psychological Aspects of Hereditary Cancer Risk Counseling and Genetic Testing: Toward an Expanded and More Equitable View -- Meaning-Centered Psychotherapy -- Quality of Life -- Bringing It All Together.
Keywords: Internal medicine; Clinical psychology; Psychiatry; Family medicine; Internal Medicine; Clinical Psychology; Psychiatry; Internal Medicine; General Practice and Family Medicine; Neoplasms -- psychology; Patient Participation -- psychology; Adaptation, Psychological